The Relative Volatility of Commodity Prices : A Reappraisal - Arezki, Rabah; Lederman, Daniel; Zhao, Hongyan (2012)
This paper studies the volatility of commodity prices on the basis of a large dataset of monthly prices observed in international trade data from the United States over the period 2002 to 2011. The conventional wisdom in academia and policy circles is that primary commodity prices are more volatile than those of manufactured products, although most of the existing evidence does not actually attempt to measure the volatility of prices of individual goods or commodities. The literature tends to focus on trends in the evolution and volatility of ratios of price indexes composed of multiple commodities and products. This approach can be misleading. Indeed, the evidence presented in this paper suggests that on average prices of individual primary commodities are less volatile than those of individual manufactured goods. However, the challenges of managing terms of trade volatility in developing countries with concentrated export baskets remain.